PROSPECTIVE TECHNICAL MEANS FOR ASSESSING THE SCALE OF DAMAGE FROM RADIATION AND CHEMICAL EXPOSURE - Abdukhakhar Shamsiyevich Ziyadullaev; Farhod Tulkinovich Norgitov (Web of Journals Publishing, 2025)
This article analyzes the prospective development of technical means for identifying and assessing the scale of damage under nuclear and chemical contamination conditions.
Keywords: Nuclear damage, chemical damage, damage, radiation, chemical фтв biologic (RKB) protection, radiation and chemical situation, radiation reconnaissance, ionizing radiation sources, airborne gamma-neutron reconnaissance set, ground-based gamma-neutron reconnaissance set, ground-based computational technical means set.